Investigating the Nigerian small and medium enterprises (SMEs)-banking long-term relationship building. Issue 1 (5th February 2018) - Ojeme, Mark; Robson, Andrew; Coates, Nigel
Abstract : Purpose: The purpose of this paper is to evaluate the role of the commitment between small and medium enterprises (SMEs) and their banks in Nigeria from the perspective of the senior SME employees. The antecedents to, and outcomes from, commitment that underpin these crucial business-to-business (B2B) relationships are quantified as part of a proposed relationship model. Design/methodology/approach: In total, 850 SMEs located across three Nigerian regions were targeted leading to the achievement of 491 complete surveys. The data collected comprised various validated items from which scales were developed. Data collection was supported by means of face-to-face interviews with senior SME representatives. Confirmatory factor analysis and structural equations modelling (SEM) were employed to validate the research model and quantify the associated relationships. Findings: Two dimensions of commitment are relevant here, namely, the affective and calculative components. The key respective antecedents to these commitment dimensions are trust and social bonding for affective commitment and costs related to benefit loss for calculative commitment. Affective commitment has the greater marginal effect on SMEs' behavioural intentions towards their banks. Research limitations/implications: The research could be expanding further in future studies through consideration of the banks' perspectives alongside those of the SMEs as consumers. Originality/value: This lies in the assessment of the relationships' strengths and characteristics from the perspectives of SMEs as clients, a sector under-represented in relationship marketing research and in a location where B2B relationships have perhaps not been fully supported by their banking sector.